2018
DOI: 10.1002/adma.201805769
|View full text |Cite
|
Sign up to set email alerts
|

Truly Concomitant and Independently Expressed Short‐ and Long‐Term Plasticity in a Bi2O2Se‐Based Three‐Terminal Memristor

Abstract: STP), which modulates the synaptic transmission efficacy dynamically at the conveying transients but leaves the efficacy unchanged during steady-state transmission; and long-term plasticity (LTP), which, in contrast, renders stable changes in the synaptic transmission efficacy. The STP and LTP have different computational uses: STP has profound effects on motor control, speech recognition, and working memory, while LTP is essential to encoding of spatial information. [2] In many if not all cases, a single plas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 55 publications
0
80
0
Order By: Relevance
“…[1][2][3] Bismuth oxyselenide (Bi 2 O 2 Se), a semiconducting 2D material featured by narrow bandgap (≈0.8 eV), high electronic mobility (20 000 cm 2 V −1 s −1 at 2 K), and good air stability, shows great potential for applications in high-performance electronics, optoelectronics, and flexible devices. [4][5][6][7][8][9][10] For example, the photodetectors based on Bi 2 O 2 Se with ultrabroadband responses, [7] high on/off ratio, and ultrahigh photodetectivity [8] have been demonstrated. Bi 2 O 2 Se is also an important material to fabricate three-terminal memristors with high speed and low energy consumption for neuromorphic functions.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Bismuth oxyselenide (Bi 2 O 2 Se), a semiconducting 2D material featured by narrow bandgap (≈0.8 eV), high electronic mobility (20 000 cm 2 V −1 s −1 at 2 K), and good air stability, shows great potential for applications in high-performance electronics, optoelectronics, and flexible devices. [4][5][6][7][8][9][10] For example, the photodetectors based on Bi 2 O 2 Se with ultrabroadband responses, [7] high on/off ratio, and ultrahigh photodetectivity [8] have been demonstrated. Bi 2 O 2 Se is also an important material to fabricate three-terminal memristors with high speed and low energy consumption for neuromorphic functions.…”
Section: Introductionmentioning
confidence: 99%
“…Applying a positive V tg pulse causes O 2− migration from top dielectric layer (AlO x ) toward top gate electrode. Zhang et al demonstrated a Bi 2 O 2 Se-based synaptic device (Figure 8b) [70] with top gate as presynaptic terminal. The role of V bg in controlling device behaviors assembles that of neuromodulator (chemical messages to change activity of synapses) in synaptic plasticity transition between excitatory to inhibitory.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…[86] The use of wide bandgap (PEA) 2 PbBr 4 (40 nm) reduces the operating current down to ≈pA. [70] Copyright 2019, John Wiley & Sons, Inc. e,f) Reproduced with permission. Cascading multiple memristive devices together though sharing electrodes allows for the independent formation and breaking of filaments in different active layers of different devices.…”
Section: Vertical Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, for the first time, the intrinsic thermal properties of 2D Bi 2 O 2 Se were revealed (about 1 W · m −1 · k −1 ). Li's group firstly used 2D Bi 2 O 2 Se for memristors [179]. In their report, truly concomitant shortterm and long-term plasticities were firstly demonstrated, opening up the prospects for ultrathin, high-speed and low-power neuromorphic devices.…”
Section: Bi 2 O 2 Sementioning
confidence: 99%